Study of Nonlinear Periodic Optical System - Alatas, H.; Iskandar, A.A.; Tjia, M. O.; Valkering, T.P. (Journal of Mathematical and Fundamental Sciences, 2019)
We give a brief review of some results of our study on one-dimensional shallow nonlinear Bragg grating with nonlinear modulation and deep nonlinear Bragg grating.